Brain pH Imaging and its Applications. (15th October 2021) - Kim, Hahnsung; Krishnamurthy, Lisa C.; Sun, Phillip Zhe
Highlights: A concise overview of pH spectroscopy (MRS), spectroscopy imaging (MRSI) and imaging (MRI) measurement techniques. pH-sensitive imaging with chemical exchange saturation transfer (CEST) MRI. Examples of extracellular pH measurement in tumor with Biosensor Imaging of Redundant Deviation in Shifts (BIRDS) MRSI. Examples of intracellular pH measurement in acute stroke with amide proton transfer (APT) MRI. Abstract: Acid–base homeostasis and pH regulation are critical for normal tissue metabolism and physiology, and brain tissue pH alters in many diseased states. Several noninvasive tissue pH Magnetic Resonance (MR) techniques have been developed over the past few decades to shed light on pH change during tissue function and dysfunction. Nevertheless, there are still challenges for mapping brain pH noninvasively at high spatiotemporal resolution. To address this unmet biomedical need, chemical exchange saturation transfer (CEST) MR techniques have been developed as a sensitive means for non-invasive pH mapping. This article briefly reviews the basic principles of different pH measurement techniques with a focus on CEST imaging of pH. Emerging pH imaging applications in the tumor are provided as examples throughout the narrative, and CEST pH imaging in acute stroke is discussed in the final section.